1992
DOI: 10.1007/bf00175142
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m hexamethylpropylene amine oxime single photon emission tomography in febrile convulsions

Abstract: We report our initial experience with technetium-99m hexamethyl propylene amine oxime (99mTC-HMPAO) brain single photon emission tomography (SPET) in the investigation of 19 children presenting with febrile convulsions. Two patients with complex febrile convulsions showed focal SPET lesions contralateral to the neurological deficit. However, in 9 out of 17 patients with simple febrile convulsions, focally disturbed perfusion was shown. In 4 out of 6 patients with electroencephalogram (EEG) abnormalities on adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In a previous study, 9 of 17 patients with simple febrile seizures exhibited abnormal SPECT findings on days 2 to 21 after seizure onset; both (2 of 2) patients with complex febrile seizures also exhibited abnormal SPECT findings 14 days after seizure onset. 6 In a recent study, the authors evaluated 127 Japanese pediatric patients clinically suspected as having initial-stage acute encephalopathy. The authors focused on patients with symptoms indistinguishable between complex febrile seizures and acute encephalopathy; in 9 of 14 such patients, SPECT findings revealed areas of hypoperfusion on days 1-13 after seizure onset ( Figure 2).…”
Section: Discussion Spectmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, 9 of 17 patients with simple febrile seizures exhibited abnormal SPECT findings on days 2 to 21 after seizure onset; both (2 of 2) patients with complex febrile seizures also exhibited abnormal SPECT findings 14 days after seizure onset. 6 In a recent study, the authors evaluated 127 Japanese pediatric patients clinically suspected as having initial-stage acute encephalopathy. The authors focused on patients with symptoms indistinguishable between complex febrile seizures and acute encephalopathy; in 9 of 14 such patients, SPECT findings revealed areas of hypoperfusion on days 1-13 after seizure onset ( Figure 2).…”
Section: Discussion Spectmentioning
confidence: 99%
“…Cytokines are considered to be involved in the pathogenesis of febrile seizures and acute encephalopathy. 5 10 For initial diagnosis of acute encephalopathy, the authors had previously reported that single-photon emission computed tomography (SPECT) might not be suitable by differentiating acute encephalopathy from convulsive disorders with pyrexia. 5 However, SPECT studies in patients with febrile seizures are very limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 In another study, approximately half (11/19) the patients with febrile seizures exhibited areas of hypoperfusion on 2 to 21 days after seizure onset. 22 Patients with febrile seizures may frequently exhibit abnormal SPECT findings. In patients with epilepsy, the region of origin of the epilepsy is detected as an area of hyperperfusion during the ictal phase and as an area of hypoperfusion during the interictal phase.…”
Section: Discussionmentioning
confidence: 99%